(NkOORDINACIQ I KATALIZ POLIMERIZACII OLEFINOW (B/s - (NvUBANOW(B, (NbULAT aHMETOWI^s; (NzAWOROHIN(B, (NnIKOLAJ dMITRIEWI^s; (NiNSTITUT HIMI^ESKIH NAUK an kAZAHSKOJ ssrs ((NaLMA(B-(NaTA (B:s (NnAUKA(B. (NkAZssr(B,s, 1987)
(NbIBLIOGR(B. (NW KONCE GLAWs
Keywords: (NpOLIMERIZACIQs; (NhIMIQ POLIMEROWs